2004
DOI: 10.26719/2004.10.6.844
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary intervention for reducing malnutrition among children in the Islamic Republic of Iran

Abstract: A multidisciplinary intervention to reduce protein-energy malnutrition among children in rural areas was piloted in 3 provinces of the Islamic Republic of Iran. Based on an initial situation analysis, a range of interventions were implemented through local nongovernmental organizations, including nutrition, health and literacy education for mothers, improved growth monitoring and fostering rural cooperatives and income generation schemes. Malnutrition before and after the intervention [in 1996 and 1999] was as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(2 citation statements)
references
References 3 publications
1
1
0
Order By: Relevance
“…The scale was applied on a sample study consisted of (30) female workers in special education centers who were divided evenly into two control groups and experimental groups, each group consist of (15) member.To analyze the results, the researcher used(T-test) to detect the differences between the two group and (2-way ANOVA). The results showed that there were significant differences at the level (α≤0.05) between the experimental and control groups for the experimental group refers to the training program on the primary health care skills scale The results of the study agrees with (Ghoneim,et al;2004), (Sheikohleslam, et al;2004), (Falks&Henequen, 2008 and (Al Lahibi, 2009). On other hand, the study shoed that there were no significant differences at the level (α≤ 0.05) between the experimental and control groups on the primary health care skills scale refers to the worker experience.…”
supporting
confidence: 83%
“…The scale was applied on a sample study consisted of (30) female workers in special education centers who were divided evenly into two control groups and experimental groups, each group consist of (15) member.To analyze the results, the researcher used(T-test) to detect the differences between the two group and (2-way ANOVA). The results showed that there were significant differences at the level (α≤0.05) between the experimental and control groups for the experimental group refers to the training program on the primary health care skills scale The results of the study agrees with (Ghoneim,et al;2004), (Sheikohleslam, et al;2004), (Falks&Henequen, 2008 and (Al Lahibi, 2009). On other hand, the study shoed that there were no significant differences at the level (α≤ 0.05) between the experimental and control groups on the primary health care skills scale refers to the worker experience.…”
supporting
confidence: 83%
“…Intervention was successful at improving multiple anthropometric outcomes (stunting, wasting and weight-for-age zscores [WAZ]) perhaps in part because it also included sanitation along with growth monitoring and home gardening (Sheikholeslam et al, 2004).…”
Section: Impact On Anthropometric Outcomesmentioning
confidence: 99%